Women's adoption of improved cook stoves in Timor-Leste: challenges and opportunities. Issue 8 (17th November 2017) - Nguyen, Therese Thi Phuong Tam
ABSTRACT: This article examines Timorese women's decision-making process of adoption of improved cooked stoves, using Slaski and Thurber's conceptual framework of " motivation, affordability, and level of engagement ", developed by Slaski and Thurber (2009). Despite the obvious, evidence-based socio-economic benefits of using improved cook stoves, the majority of households still persist with their traditional cooking method. This article argues that the level of engagement with new technology needs to be contextualised in light of cultural attributes and beliefs which have led to the slow uptake of clean, efficient cooking technology.